Pengaruh Retribusi Daerah Terhadap Pendapatan Asli Daerah Kabupaten Aceh Barat - Riana Desi; Linda Rahmazaniati (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
This study aims to analyze the effect of regional levies on local revenue in West Aceh Regency. With a quantitative approach, the population used is a report on the realization of regional income for the period January 2019 to December 2021. The methodology of this research uses a simple linear regression analysis mechanism using secondary data. The test results using SPSS 25 obtained that the Regional Retribution has a significant effect on the Regional Original Income of the West Aceh Regency. It is stated that the regression coefficient is 0.667, and the significant result is 0.000 < 0.05